Non-parametrical algorithm using Chentsov’s estimate for detecting radiosignal - Синицын, Р. Б. (Proceedings of National Aviation University (archive), 1999)
Considered are Chentsov’s estimates in the basis of trigonometrical functions. New non- parametric statistic hypothesis tests based on these estimates are proposed. An algorithm for detecting signals in correlated noise has been synthesized on the basis of tests proposed. The effectiveness of the algorithm is proved by the results of mathematical modelling